O42. Realizing the European Network of Biological Dosimetry 'RENEB': Results of 2 intercomparison exercises for the micronucleus assay. (September 2016) - Depuydt, J.; Baeyens, A.; Barnard, S.; Beinke, C.; Benedek, A.; Beukes, P.; Buraczewska, I.; Darroudi, F.; De Sanctis, S.; Dominguez, I.; Monteiro Gil, O.; Hadjidekova, V.; et al.
Abstract : Introduction: In the framework of the RENEB project, two intercomparison exercises were conducted to assess the suitability of the cytokinesis-block micronucleus assay, and to evaluate the capacity of a large laboratory network performing biodosimetry for radiation emergency triages. Twelve European institutions participated in the first exercise, and four non-RENEB labs were added in the second one. Materials and methods: Irradiated blood samples were shipped to participating labs, whose task was to culture these samples and provide a blind dose estimate. Micronucleus analysis was performed by automated, semi-automated and manual scoring procedures. Results: The dose estimates provided by the network laboratories were in good agreement with the true administered doses. The most accurate estimates were reported for the low dose points ( < 1 Gy). For higher dose points ( > 2.5 Gy) a larger variation in estimates was observed, though in the second exercise the number of acceptable estimates increased satisfactorily. Higher accuracy was achieved with the semi-automated method. Conclusion: The results of the two intercomparsion exercises performed by our network demonstrate that the micronucleus assay is a useful tool for large-scale radiation emergencies, and can be successfully implemented within a large network of laboratories. The results further emphasize the importance of performing regular intercomparison training exercises within a specialised biodosimetry network.